Energy potential of biochar from slow pyrolysis of mixed tree leaves in a pilot-scale fixed-bed reactor - Ibitoye, Segun E.; Alam, Meraj; Olayemi, Olalekan A.; Akinlabi, Esther T.; Sarkar, Ishita; Mahamood, Rasheedat M.; Jen, Tien-Chien; Loha, Chanchal (International Journal of Renewable Energy Development, 2025)
Thermochemical conversion processes, such as pyrolysis, offered significant potential for harnessing energy from biomass as a substitute for conventional fuels. This study investigated energy generation from mixed tree leaves through pyrolysis. The pyrolysis was conducted at 3 temperatures: 400, 500, and 600 °C. Characterization of the feedstock and pyrolysis products was carried out following international standards. The results showed that bio-oil yields (26.13–39.95%) and syngas yields (30.33–39.38%) increased with temperature, while the char yield decreased from 43.66-29.67%. The FC VM, AC, and MC of the biochars varied from 61.26-67.71, 4.58-12.75, 21.32-25.32, and 2.39-4.67%, respectively. After pyrolysis, the highest C (67.71%) was obtained at 600 °C, while the highest H (3.98%) was recorded at 400 °C. The study revealed that FC, AC, and C increased with temperature, whereas MC, VM, H, and O decreased. The produced biochars, particularly Char600, demonstrated HHV values (up to 23.32 MJ/kg), improved FC, and enhanced BET surface areas. While slightly lower than the HHV of traditional metallurgical coke, the biochars showed strong potential for partial substitution or co-injection in high-temperature metallurgical processes. The enhanced porosity and C contribute to their suitability as renewable solid fuels, supporting carbon footprint reduction in heavy industries.